2020
DOI: 10.1111/raq.12406
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of carrying capacity for bivalve mariculture in subtropical and tropical regions: the need for tailored management tools and guidelines

Abstract: In a context of increasing global food demand, the aquaculture sector, and more particularly bivalve mariculture, has expanded significantly. While the impact of bivalve mariculture was initially overlooked, it is now widely recognized that this industry can significantly impact the ecosystem and its services. Carrying capacity assessment tools have been developed accordingly and have proved to be a useful and efficient aid for mariculture management. However, carrying capacity assessment tools have been mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…Our study is justified on the basis of the scarce research works on Spanish aquaculture activities that can be found in the literature, despite being the leading producer in the European Union. Most works on this topic are still at a development stage, and, consequently, further studies are still required [21] to realise the necessary development of this industry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study is justified on the basis of the scarce research works on Spanish aquaculture activities that can be found in the literature, despite being the leading producer in the European Union. Most works on this topic are still at a development stage, and, consequently, further studies are still required [21] to realise the necessary development of this industry.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, in coming years, as further lines of research are covered, we will apply more complex and advanced techniques that will enrich these conclusions, even by combining them with experiments in social laboratories. According to the index obtained, these kinds of indicators have always a risk of excessive simplification [21]. We can develop them more deeply in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suspended canopy layer inhibits the surface layer water flow, therefore, change the circulation pattern inside and around the farm (Konstantinou et al, 2015;Lin et al, 2016;Konstantinou and Kombiadou, 2020;Liu and Huguenard, 2020). The flow responses to the presence of farm in turn affect the mussel food availability through increased water residence time and nutrient depletion, therefore, the carrying capacity of ecosystem (Byron et al, 2011a;Byron et al, 2011b;Anaïs et al, 2020;Gao et al, 2020). Quantifications of effect of suspended farms on circulation is critical in evaluating carrying capacity, ecosystem sustainable and effective management of the aquaculture activities (Filgueira et al, 2015;Froján et al, 2018;Konstantinou and Kombiadou, 2020).…”
Section: Introductionmentioning
confidence: 99%